Total Synthesis of the Fungal Metabolite Trienylfuranol A through Nucleophilic Diastereodivergent Additions to Oxocarbenium Ions. Issue 13 (7th April 2021) - Arcile, Guillaume; Retailleau, Pascal; Ouazzani, Jamal; Betzer, Jean‐Francois
Abstract: Herein, we describe the first total synthesis of trienylfuranol A, a fungal triene‐substituted tetrahydrofuran metabolite. The stereoselectivity of the chiral center bearing the trienyl side chain was diastereodivergently controlled by the addition of nucleophilic species on substituted γ‐butyrolactone. Remarkably, the C ‐nucleophilic species or hydride addition onto oxocarbenium intermediate leads to the opposite diastereoselectivity reported for Kishi or Woerpel models. The use of Hantzsch ester (HEH) as organic hydride donor has enabled us to obtain the desired stereochemistry. The total synthesis of trienylfuranol A was achieved in 8 steps from acetaldehyde and pyruvic acid. Abstract : The first total synthesis of trienylfuranol A, a fungal terminal triene‐substituted tetrahydrofuran metabolite is described. The key step, for the installation of the stereogenic center of the trienyl side chain, involves a stereofacially reduction of oxocarbenium ions directed by the hydride donor.